Suramin inhibits death receptor-induced apoptosis in vitro and fulminant apoptotic liver damage in mice - Eichhorst, Sören; Golks, Alexander; Krammer, Peter H. (Nature medicine, 2004)
Suramin is a polysulfonated derivative of urea and has been widely used both to treat infections and as a chemotherapeutic drug. Suramin has been shown to inhibit growth factor signaling pathways; however, its effect on apoptosis is unknown. Here we show that suramin inhibits apoptosis induced through death receptors in hepatoma and lymphoma cells. It also inhibits the proapoptotic effect of chemotherapeutic drugs. The antiapoptotic mechanism is specific to cell type and is caused by reduced activation, but not altered composition, of the death-inducing signaling complex (DISC), and by inhibition of the initiator caspases 8, 9 and 10. Suramin also shows similar effects in in vivo models: apoptotic liver damage induced by CD95 stimulation and endotoxic shock mediated by tumor-necrosis factor (TNF) are inhibited in mice, but necrotic liver damage is not inhibited in a rat model of liver transplantation. Thus, the antiapoptotic property of suramin in the liver may be therapeutically exploited.
Gesehen am 06.04.2021